Conceptualisation of global citizenship, intercultural competence, and domestic internationalisation in enhancing graduates’ global employability - Anees Janee Ali,; Awang Rozaimie,; Khalid, Jamshed; Nurul Hidayah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The global graduate skills gap in the 21st century has been considered a global and significantly widespread issue. There is a shortfall in skill attainment across the board, as well as a mismatch in expectations among students and employers, especially for the global employability quest. Stiff challenges for global job mobility strain the higher education institutions, especially in Malaysia, to revise their academic and practical curriculum in preparing graduates to meet global employability requirements. Thus, this paper mainly proposes the graduates’ global employability paradigm, which is reflected by the internationalisation process, which is moderated by the institutional support. This paper reviews scholarly studies that use a thematic inquiry. The Malaysia Critical Occupations List (MyCOL) has identified a skills gap, particularly among Malaysian graduates. This paper thematically highlights the ways in which graduates' global employability is believed to be influenced by internationalisation at home (IaH), intercultural competency, global citizenship, and institutional support. Therefore, by engaging graduates to be more marketable globally based on their skills and academic backgrounds, HEIs, stakeholders, and the government work together to mitigate the effects of the global digital economy.